Perception of undergraduate students of a Brazilian University about the Biochemistry course - Pablo Andrei Nogara (Journal of Biochemistry Education, 2018)
Biochemistry is an essential science that deals with the chemical bases of life, being an important discipline for several areas. Thus, the objective of this work was to evaluate the opinion of students about the Biochemistry course. An instrument, involving questions about the discipline, the professors, the monitors, and a self-evaluation was applied to 231 students from 12 undergraduate courses, divided into 3 areas of knowledge: Natural, Health and Rural Sciences. The majority of the students answered that they consider Biochemistry an important discipline, but they presented a reasonable comprehension of the contents, probably by a lack of chemical skills. The students consider the credit hour of the discipline sufficient but badly used. They said that the Professor performance is reasonable to good, and miss a correlation between the class and the professional acting, especially in the Rural Science. This study showed that the Biochemistry classes need to be rethought for the areas of action of each course. In addition, the students' basic pre-knowledge should be improved.